Pivoting from systems “thinking” to systems “doing” in health systems—Documenting stakeholder perspectives from Southeast Asia - Srivastava, Siddharth; Nambiar, Devaki (Frontiers in Public Health, 2022)
Applications of systems thinking in the context of Health Policy and Systems Research have been scarce, particularly in Low- and Middle-Income Countries (LMICs). Given the urgent need for addressing implementation challenges, the WHO Alliance for Health Policy and Systems Research, in collaboration with partners across five global regions, recently initiated a global community of practice for applied systems thinking in policy and practice contexts within LMICs. Individual one on one calls were conducted with 56 researchers, practitioners & decision-makers across 9 countries in Southeast Asia to elucidate key barriers and opportunities for applying systems thinking in individual country settings. Consultations presented the potential for collaboration and co-production of knowledge across diverse stakeholders to strengthen opportunities by applying systems thinking tools in practice. While regional nuances warrant further exploration, there is a clear indication that policy documentation relevant to health systems will be instrumental in advancing a shared vision and interest in strengthening capacities for applied systems thinking in health systems across Southeast Asia.